Pengaruh Lingkungan Kerja Non Fisik dan Disiplin Kerja Terhadap Kinerja Pegawai.Puskesmas Keramasan Palembang - Miranda Miranda; Hamid Halin; Meilin Veronica (Universitas Batanghari Jambi, 2023)
The purpose of this study was to determine the effect of the work environment and work discipline on employee performance at the Palembang Keramasan Health Center. This research was conducted by Palembang Keramasan Health Center officers, totaling 52 people. The type of research used is quantitative research by distributing questions in the Google Form. Sampling using saturated sampling technique that uses the entire population of 52 respondents. As the basis for the data in this study using primary and secondary data. According to the results of the t test indicate that the workplaces of agencies are not the same. tcount 2.019 > ttable 2.009 with a significance level less than 0.05, namely 0.049, which means Ho is rejected and Ha is accepted. This shows that partially the Non-Physical Work Environment has a positive and significant effect on Employee Performance and Work Discipline with the acquisition of a positive coefficient value tcount 2.148 > ttable 2.009 with a significant level less than 0.05, namely 0.037, which means Ho is rejected and Ha is accepted. This shows that work discipline partially has a positive and significant effect on employee performance. Then the results of the F test analysis (Simultaneous) obtained an Fcount value of 49.043 > Ftable 3.18 with a significance level of less than 0.05, namely 0.000. So it can be concluded that Ho is rejected and Ha is accepted, which means that the non-physical work environment (X1) and work discipline (X2) simultaneously have a positive effect on employee performance (Y). The results of the analysis of the coefficient of determination (R2) obtained a coefficient value of R Square (R2) of 0.667 or 66.7%. It can be concluded that the percentage of non-physical work environment (X1) and work discipline (X2) on employee performance (Y) is 0.667 or 66.7%.